PENGARUH KOMUNIKASI INTERPERSONAL TENAGA KESEHATAN TERHADAP KEPUASAN PASIEN DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING - AFAQ UMUDY, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2016)
Good interpersonal communication and harmony is created between health personals with patients could generate more confidence in patients’s mind which in turn will boost satisfaction. This research is a quantitative one with a judgmental sampling. Data obtain from respondents as many as 110 respondents. Measurement scale in this study used a Likert scale. Statistical analysis to gain result of research was path analysis using the software AMOS 21. The research shows that interpersonal communication had a significant effect toward trust. Patient’s belief had significant effect toward satisfaction. Interpersonal communication didn’t have any significant effect toward satisfaction, but the trust is able to mediate the role of interpersonal communication that suppresses significant influence toward satisfaction. Keywords: interpersonal communication, trust, satisfaction.